2012
DOI: 10.1175/jcli-d-11-00570.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Regional Global Climate Model Water Vapor Bias and Trends Using Precipitable Water Vapor (PWV) Observations from a Network of Global Positioning Satellite (GPS) Receivers in the U.S. Great Plains and Midwest

Abstract: Precipitable water vapor (PWV) observations from the National Center of Atmospheric Research (NCAR) SuomiNet networks of ground-based global positioning system (GPS) receivers and the National Oceanic and Atmospheric Administration (NOAA) Profiler Network (NPN) are used in the regional assessment of global climate models. Study regions in the U.S. Great Plains and Midwest highlight the differences among global climate model output from the Fourth Assessment Report (AR4) Special Report on Emissions Scenarios (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Validation data is obtained by estimating regional monthly mean values from the SuomiNet GPS network [4]. Details of this regional GPS estimation are presented in Roman et al [1]. Fig.…”
Section: Airs Pwv Diurnal Sampling Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…Validation data is obtained by estimating regional monthly mean values from the SuomiNet GPS network [4]. Details of this regional GPS estimation are presented in Roman et al [1]. Fig.…”
Section: Airs Pwv Diurnal Sampling Validationmentioning
confidence: 99%
“…The GCM predicted 100 year trend in PWV for the Oklahoma region is 0.05 mm/yr [1]. In this section we make use of the stability of the GPS system to assess the trend error in the AIRS PWV measurements at the U.S. Southern Great Plains region.…”
Section: Airs L3 Pwv Climatology Trend Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional techniques of IWV sounding such as radiosondes and satellite and ground-based radiometric systems give very limited data for the understanding of these processes. Moreover, long time series of high-precision IWV data are necessary for climate change monitoring and calibration of other techniques (Roman et al, 2012). Therefore, in the last two decades, ground-based receivers of GPS signals have begun to be used as IWV sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, GPS-derived PWV data can be used as an independent data source to evaluate and correct the output results of a model so as to further improve the output precision. Using GPS-PWV data for the Great Plains in the mid-western United States, Roman et al [12] systematically assessed the water vapor data obtained from various global climate models and determined the water vapor errors under various models through comparison, thus improving the precision in the water vapor outflow in global and regional climate models to a certain extent. Bennitt et al [13] assimilated GPS-derived zenith total delay (ZTD) data into a numerical weather forecast model and found that such assimilation improved the performance of cloud prediction to a certain degree.…”
Section: Introductionmentioning
confidence: 99%